Penerapan Homeletika dalam Pembinaan Rohani kepada Anak PAUD Ananda Silangkitang “Hidup Dalam Kasih” dalam Roma 12:9a - Ester Viona Sihotang; Stefani Hagelara Pakpahan; Inneh Siera Nainggolan; Melina Agustina Sipahutar (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Proclaiming the truth of God's Word is the duty of all of us as disciples of Christ. Even though we have different ways of expressing it, we have to do it for all age groups. Likewise with children, spiritual formation must be carried out to guide, grow and build the child's spiritual identity. Living in love is one of the teachings that we often hear in Christianity, as well as for children, it is very important to carry out spiritual formation so that they can learn how to live in true love.